Strukturni in upravljalski dejavniki družbene kohezije, zaupanja in participacije v spletnih skupnostih - Petrič, Gregor (Družboslovne razprave, 2008)
This paper deals with the social structures and processes that enable Internet-based group communication spaces to develop from social aggregates to a social form also known as an online community. The paper focuses on three anchors of online communities - social cohesion, trust and participation - which underlie community reproduction and sustainability and, at the same time, are sources of knowledge, social relationships and identification for their members. The impact of regulation and self-presentation processes on three anchoring elements in online communities is considered. Drawing on the conceptual discussion, an explanatory model is proposed that establishes the dependency of the anchoring elements on administrator decisions and the availability of regulation and self-presentation processes. The paper presents an exhaustive operationalisation of factors at the level of community characteristics that stem from administrative decisions and result from social interactional dynamics within an online community. The results of multiple regression analyses carried out on a sample of 61 Slovenian web forums suggest that social cohesion, trust and participation in online communities are mostly influenced by social structures that emerge from group interactional dynamics and to a lesser extent by administrative decisions, which may also give rise to undesired latent consequences.
Keywords: Svetovni splet; World Wide Web; Communication; Komuniciranje; Navidezne skupnosti; Virtual communities; Social cohesion; Družbena kohezija; Trust; Zaupanje; Participacija; Participation; družbena omrežja